Potential of smart irrigation controllers for demand-side management of water distribution systems - Nathan T. Lunstad; Robert B. Sowby (Energy Nexus)
As a demand-side management (DSM) tool, smart irrigation controllers (SICs) have the potential to help water utilities manage peak demands. With an EPANET hydraulic model we demonstrate that residential SICs can shift and shave peak demands for outdoor irrigation. A real pressurized irrigation system was modeled with demands on a Monday-Wednesday-Friday schedule (baseline scenario) compared to a Monday-Wednesday-Friday and Tuesday-Thursday-Saturday schedule (intervention scenario). With the intervention, the system has lower peak demand (49 % reduction) and improved pressures (9.5 % increase in nodes satisfying minimum pressure). Without intervention, costly capital facility improvements would be needed to maintain the same level of service. Literature suggests SIC can provide 15 % to 40 % water savings; a third scenario assuming 30 % conservation with SICs (intervention SIC scenario) would shift and shave demand (65 % reduction in peak demand) as well as deliver benefits in pressure management (10 % increase in nodes satisfying minimum pressure), energy use (28 % reduction in peak power and 13 % reduction in energy cost), and distribution capacity (9.5 % decrease in pipes with high velocity) relative to the baseline scenario. This is the first hydraulic model analysis to demonstrate the DSM effectiveness of SICs.